PENGARUH KUALITAS LAYANAN, KEPERCAYAAN, DAN KEAMANAN TERHADAP KEPUASAN PELANGGAN DOMPET DIGITAL DANA (Studi Kasus Pengguna DANA di DKI Jakarta) - Reihan Fito Ananta (2022)
The development of technology is now a positive thing because it can make it easier for someone in everything to be easier and faster, especially in digital transactions, therefore these demands present innovations in the field of financial technology, namely digital wallets that provide convenience in conducting transactions and digital payments. This study aims to test and prove whether there is a partial effect of service quality, trust and security on customer satisfaction with the DANA digital wallet. The object of this study are DANA digital wallet users who have made more than 2 transactions and are domiciled in DKI Jakarta. This research uses primary data and is a quantitative research. The sampling technique uses non-probability sampling with purposive sampling method with an error rate of 5%. The data source was obtained by distributing questionnaires to 100 respondents via the Google Form. Data analysis techniques used in this research are descriptive and inferential data analysis techniques. Based on the results of data processing using the SmartPLS 3.0 software test tool with path coefficient analysis techniques, it can be shown that (1) service quality has a significant effect on customer satisfaction with a path coefficient value of 0.460. (2) trust has a significant effect on customer satisfaction with a path coefficient value of 0.314. (3) security has no significant effect on customer satisfaction with a path coefficient value of 0.079.